2021
DOI: 10.1515/med-2020-0183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydroxyethyl starch and gelatin on the risk of acute kidney injury following orthotopic liver transplantation: A multicenter retrospective comparative clinical study

Abstract: Objectives This multicenter retrospective study aimed to compare the effects of HES and gelatin (GEL) on the risk of post-OLT AKI. Method A total of 1,672 patients undergoing OLT were enrolled from major transplant centers in China between 2005 and 2013. These patients were divided into three groups: GEL, hydroxyethyl starch (HES), and GEL + HES group. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Both colloids and crystalloids can be used in GDFT protocol. Previous studies showed that intraoperative colloid usage was not associate with an increased risk of AKI after cardiac surgery [31], liver transplantation surgery [32], and thoracoscopic lobectomy [22]. Meta-analysis showed that postoperative kidney dysfunction was similar between colloid-based GDFT and crystalloid-based GDFT after major noncardiac surgery [33].…”
Section: Discussionmentioning
confidence: 99%
“…Both colloids and crystalloids can be used in GDFT protocol. Previous studies showed that intraoperative colloid usage was not associate with an increased risk of AKI after cardiac surgery [31], liver transplantation surgery [32], and thoracoscopic lobectomy [22]. Meta-analysis showed that postoperative kidney dysfunction was similar between colloid-based GDFT and crystalloid-based GDFT after major noncardiac surgery [33].…”
Section: Discussionmentioning
confidence: 99%
“…Though HES has adverse effect in severe sepsis patients and intensive care patients (Perner et al 2012 ; Myburgh et al 2012 ), but the pathophysiology was different between sepsis and operation patients. A study of 11,691 patients who underwent elective noncardiac surgeries showed that the intraoperative use of moderate doses of 6% HES 130/0.4 was not associated with increased risk of AKI (Degoul et al 2020 ), as while as in cardiac surgery (Nagore et al 2021 ) and liver transplantation surgery (Chen et al 2021 ). The recent meta-analysis also showed that HES was shown to be safe and efficacious in the perioperative setting (Chappell et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%